Mengenal Bahasa Pemrograman Pada Algoritma Pemrograman - Fadilah Aulia; Yahfizham (CV. ITTC INDONESIA, 2024)
A programming algorithm is a coherent progression that is followed to address a specific problem or task. A programming language is a guide used to convey tasks to a computer. Programming languages ​​include: C, C++, Java, Python, JavaScript. Each programming language has its own advantages and disadvantages. This article is expected to provide a broad understanding of the programming languages ​​used in programming algorithms. The method used is a literature study which presents a programming language that is easiest to learn for beginners.